Unraveling Early Signs of Navigational Impairment in APPswe/PS1dE9 Mice Using Morris Water Maze - Karunakaran, Smitha (Frontiers in Neuroscience, 2020)
Mild behavioral deficits, which are part of normal ageing, can be early indicators of impending Alzheimer’s disease. Using the APPswe/PS1dE9 (APP/PS1) mouse model of Alzheimer’s disease, we utilized the Morris water maze spatial learning paradigm to systematically evaluate mild behavioral deficits that occur during early stages of disease pathogenesis. Conventional behavioral analysis using this model indicates that spatial memory is intact at 2 months of age. In this study, we used an alternative method to analyze behavior of the mice, aiming to gain a better understanding of the nature of cognitive deficits by focusing on the unsuccessful trials during water maze learning rather than successful ones. APP/PS1 mice displayed a higher number of unsuccessful trials during the initial days of training, unlike their wild type counterparts. However, with repeated trial and error, learning in APP/PS1 reached levels comparable to that of wild type mice during later days of training. Individual APP/PS1 mice preferred a non-cognitive search strategy called circling, which led to abrupt learning transitions and an increased number of unsuccessful trials. These findings indicate the significance of subtle intermediate readouts as early indicators of conditions such as Alzheimer’s disease.